FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI PETERNAK TERHADAP PEMANFAATAN JERAMI PADI SEBAGAI PAKAN DI KECAMATAN BANTIMURUNG - Sitti Sohrah; Syahdar Baba (Jurnal Ilmu dan Teknologi Peternakan, 2019)
Research on the use of rice straw as a feed has been widely done but the adoption at the farmer’s business level is still low. Perception of the farmers is one of the key factors in increasing the adoption of rice straw utilization as a feed. The aims of this study were to determine the level of farmers’ perceptions of the use of rice straw as a feed and factors that affect it. The study was conducted in the Bantimurung sub-district, which is the center of beef cattle and technical irrigated lowland rice. The number of respondents was 65 people who were randomly selected out of 325 farmers (20% of the population) by enumerators who had been trained. The variable measured was the level of perceptions of the farmers in fulfilling the livestock needs and the ability of the farmers in providing rice straw as a feed. The independent variable included the socio-economic factors of the farmers, consisting of age, number of livestock, number of family members, number of rice fields area, and level of education. Data were analyzed using multiple regression models using the F and t-test. The results showed that the level of perception of the farmers in fulfilling livestock needs was in less category. The level of perceptions of the farmers towards their ability in providing rice straw as feed was in the high category. Factors that influence their level of perception were the number of livestock and the number of family members. The number of livestock had a negative effect (P< 0.01) on the level of farmer perception, in which the higher the number of livestock owned by the farmers, the less level of the farmer's perception towards the use of rice straw as feed. The number of the family had a positive effect (P<0.01) on the level of the farmer perception meaning that the higher the number of the family members, the higher the level of the farmer's perception towards the use of rice straw as a feed.